2007
DOI: 10.1086/522026
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Particle Drifts by Turbulence

Abstract: We present results from direct numerical simulations showing the suppression of the large-scale drift motion of an ensemble of charged particles in a nonuniform turbulent magnetic field. We find that when scattering is negligible, the ensemble average drift velocity is in the direction predicted by the usual guiding center theory. When scattering is very strong, we find that all large-scale drift motions vanish. For an intermediate amount of scattering we find that the antisymmetric drift velocity is typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 27 publications
10
91
0
Order By: Relevance
“…In particular, the GG is well detected in CR intensity during the maximum phase of all solar cycles and delayed, with respect to SA, on average of about 6 months. The time lags observed near the sunspot maximum could be due to an efficient diffusion in such periods, when enhanced fluctuations in the magnetic field are expected, while the drift effects should be suppressed (e.g., Minnie et al 2007). The similarity between the CR and SA profiles confirms that the CR variability, at these timescales, is related to the ∼11 yr solar activity cycle (including QBOs), whose representative index is the SA.…”
Section: Solar Modulation Versus Drift Effectsmentioning
confidence: 99%
“…In particular, the GG is well detected in CR intensity during the maximum phase of all solar cycles and delayed, with respect to SA, on average of about 6 months. The time lags observed near the sunspot maximum could be due to an efficient diffusion in such periods, when enhanced fluctuations in the magnetic field are expected, while the drift effects should be suppressed (e.g., Minnie et al 2007). The similarity between the CR and SA profiles confirms that the CR variability, at these timescales, is related to the ∼11 yr solar activity cycle (including QBOs), whose representative index is the SA.…”
Section: Solar Modulation Versus Drift Effectsmentioning
confidence: 99%
“…The functional form of u D is taken from Burger et al (2000), but assumed to be only 55% effective, based on A&A 522, A35 (2010) the modelling done by Potgieter (1989), Langner et al (2004) and Minnie et al (2007). Neutral sheet drift is due to the heliospheric current sheet (HCS) and as the modulation model is limited to solar minimum conditions, a HCS tilt angle of α = 10 • is assumed.…”
Section: The Modulation Modelmentioning
confidence: 99%
“…Although turbulence can suppress drifts (see Minnie et al 2007), we find a nonsymmetric behavior of particle scattering due to the assumption of nonaxisymmetric turbulence. For a flat spectrum in the energy range and for slab/2D composite geometry, we derived in particular…”
Section: Discussionmentioning
confidence: 81%
“…This motivates us to refer to these tensor elements as ''drift coefficients.'' Recently, however, Minnie et al (2007) have demonstrated, by use of a test particle code, that the drifts are usually suppressed when there is sufficiently strong turbulence. Thus, we believe that in such cases nonaxisymmetric particle scattering can be caused by nonaxisymmetric turbulence.…”
Section: Introductionmentioning
confidence: 99%